Exploitation of penaeid shrimp resources by small mechanised trawlers off Visakhapatnam, Andhra Pradesh - Maheswarudu, G.; Sreeram, Miriam Paul; Dhanwanthari, E.; Varma, J. B.; Sajeev, C. K.; Satya Rao, S. (Indian Journal of Fisheries, 2015)
Small trawlers (9-11 m OAL) fit for short-term cruises (2-7 days) exploit penaeid shrimps up to a depth of 70 m in the Bay of Bengal off Visakhapatnam both in the northern and southern directions. During the period 2001 to 2010, average annual fishing effort was 5,97,412 h. Penaeid shrimp catch varied from 703 t to 4,323 t with average catch per hour (cph) being 3.54 kg. The contribution of penaeid shrimps to total fish landings ranged from 6.7 to 18.32%, both fishing effort and landings of the resource showing increasing trend. Penaeid shrimp landing was supported by 24 species, dominated by Metapenaeus monoceros followed by Metapenaeus dobsoni. Mean annual species composition and cph for each species were estimated for two spells i.e., 2001 to 2005 and 2006 to 2010. Catch per hour for five species declined whereas it increased for the rest 19 species. The cph for penaeid shrimps increased by 103% from spell 1 to spell 2. Expected catch for each year was estimated by Schaefer production model (CEDA; r2=0.72) which showed that the resource was under exploitated during 2001-2005 and overexploited during 2006-2010, which indicate the necessity for restricting fishing effort at present level.